Pengaruh Penagihan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Wajib Ginting (Majalah Bisnis & IPTEK, 2018)
The goal of this study is finding the implementation of Personal Income Tax Collection activities at the Primary Tax Service Office in Bandung, to find out the Individual Taxpayer Compliance and find out how much the Personal Income Tax Collection Effect on Individual Taxpayer Compliance. The method used in the study at one of the Primary Tax Service Offices in Bandung is descriptive analysis method. The data collecting techniques are interviews, questionnaires and library research. The sampling technique with non-probability sampling is saturated sample, where all members of the population are sampled. The data analysis techniques are carried out through descriptive analysis and verification analysis. Based on the results of the study, personal income tax collection is considered as good with an average score of 3.27 and the individual taxpayer compliance is categorized as is good enough. The average score is 3.25. then the personal income tax collection is adequate in improving personal taxpayer compliance. It was proven by the results of the correlation coefficient analysis by using the product moment. It has powerful effect at 0.831. Personal income tax collection affects personal taxpayer compliance by 69.00%, while the remaining 31.00% is influenced by the other factors that are not examined in this study such as the condition of a country's tax administration system, service to the taxpayers, tax law enforcement, inspection taxes and tax rates.